Pengaruh Pendidikan Kesehatan dengan Media Shadow Puppet Story dan Demonstrasi CTPS terhadap Pengetahuan dan Keterampilan Anak Usia Dini - Muhammad Arkham Kholadi Pilomonu; Joko Sapto Pramono; Dian Ardyanti; Endah Wahyutri (Yayasan Literasi Sains Indonesia, 2026)
The low prevalence of handwashing with soap (CTPS) among young children puts them at risk of contracting infectious diseases such as diarrhea. Creative educational media innovations, such as shadow puppet stories and demonstrations, are needed to promote healthy behaviors in children. This study aims to analyze the effect of health education using shadow puppet stories and CTPS demonstrations on improving the knowledge and skills of young children at Purnama Loa Janan Ulu Kindergarten. This study used a pre-experimental design with a one-group pretest-posttest design. The study population consisted of all students at Purnama Loa Janan Ulu Kindergarten, with a total sample of 34 respondents. Data analysis used the Wilcoxon statistical test. Analysis of knowledge using the Wilcoxon test yielded a Sig. value of 0.0001 < (p = 0.05), indicating a significant difference between the pretest and posttest. Analysis of skills also showed a significant difference with a Sig. value of 0.0001 < (p = 0.05). There was a significant effect of the intervention using shadow puppet stories and demonstrations on the improvement of knowledge and skills regarding CTPS for early childhood.